The Role of Teachers in Slow Learner Student Learning Activities at Junior High School Level - Rihadatul'aisy, Najwa (Universitas Negeri Surabaya, 2025)
This study aims to examine the implementation of inclusive education for slow learner students at SMPN 22 Surakarta, focusing on the role of teachers in designing, implementing, and evaluating learning that is tailored to the individual needs of students. Using a qualitative descriptive approach, data were collected through in-depth interviews, classroom observations, and documentation studies. The results of the study revealed that teachers implemented various inclusive learning strategies, such as simplifying learning content, utilizing visual media, forming heterogeneous learning groups, and modifying the form and implementation of assessments. In addition, teachers actively build cooperation with parents through intensive communication to ensure the continuity of the learning process at home. These practices reflect the application of the Universal Design for Learning (UDL) principle and the Zone of Proximal Development (ZPD) theory proposed by Vygotsky. This study concludes that the success of inclusive education is not only determined by the teacher's ability to adjust pedagogical strategies, but also requires policy support from the school, continuous professional training, and close collaboration between teachers and families.